CORRELATION OF CD4 WITH TOTAL LYMPHOCYTE COUNTS IN HIV PATIENTS - Rini Riyanti (UNEJ e-Proceeding)
Worldwide estimates of people living with HumanImmunodeficiency Virus was approximately 32million in 2007 with thousands of people gettinginfected every day therapy (Obirikorang et.al,2012). Globally, 34 million people were living withhuman immunodeficiency virus (HIV) at the end of2011 (Chen et.al, 2013). Most people living withHIV are from developing countries with less than5% receiving antiretroviral therapy (Obirikoranget.al, 2012).A CD4 count is a laboratory test that measures thenumber of CD4 T lymphocytes (CD4 cells) in asample of blood. In HIV patients, it is the mostimportant laboratory indicator of how well theimmune system is working and the strongestpredictor of HIV progression. Once a person isinfected with HIV, the virus begins to attack anddestroy the CD4 cells of the person’s immunesystem. HIV uses the CD4 cells to multiply andspread throughout the body. This is the HIV lifecycle.The associated immune deficiency in humanimmunodeficiency virus (HIV) patients leading toinfection by opportunistic pathogen is ascribed todepletion of CD4. CD4 count can therefore beregarded as the accurate measurement of therobustness and functionality of the immunecapability to protect the body against generalinfection. CD4 T lymphocyte cell depletion is one ofthe hallmarks of progression of HIV infection and amajor indicator of the stage of the disease in HIVinfected individuals. World Health Organizationrecommended that most treatment initiationdecisions be guided by CD4 measurement andclinical staging.AIDS is the stage of HIV infection that occurs whenthe immune system is badly damaged and it isbecome vulnerable to opportunistic infections.When the number of your CD4 cells falls below 200cells/mm3, these are considered to haveprogressed to AIDS. (In a healthy immune system,CD4 counts are between 500 and 1,600cells/mm3.)The initiation of antiretroviral therapy is based onCD4 counts of less than 350 cells/mm3 according tothe World Health Organization (WHO) and Centrefor Disease Control (CDC). The determination ofCD4 count however in resource-limited localities isdifficult.In April 2002, the World Health Organization(WHO) suggested that total lymphocyte count(TLC) could serve as a surrogate for CD4+cell countbecause TLC is easily obtained from routinecomplete blood cell counts by multiplying thepercentage of lymphocytes by the white-blood-cellcount (Chen et.al, 2013).Total lymphocyte count(TLC) is a derived immunological marker calculatedfrom white blood cell count and relativelymphocyte count. For instance, if a patient has atotal white blood cell count of 10.0 × 10⁹/L andrelative lymphocyte count of 30% obtained fromdifferential leukocyte count, total lymphocytecount of such patient would be 3 × 10⁹/L.The aim of this study was therefore to ascertainexisting relationships between CD4 count and TLCand to further ascertain if TLC could be used as asurrogate markerfor CD4 counts.